A spotlight on alkaloid nanoformulations for the treatment of lung cancer - S. M., Sindhoor; Naveen, N. Raghavendra; Rao, GSN Koteswara; Gopan, Gopika; Chopra, Hitesh; Park, Moon Nyeo; Alshahrani, Mohammed Merae; Jose, Jobin; Emran, Talha Bin; Kim, Bonglee (Frontiers in Oncology, 2022)
Numerous naturally available phytochemicals have potential anti-cancer activities due to their vast structural diversity. Alkaloids have been extensively used in cancer treatment, especially lung cancers, among the plant-based compounds. However, their utilisation is limited by their poor solubility, low bioavailability, and inadequacies such as lack of specificity to cancer cells and indiscriminate distribution in the tissues. Incorporating the alkaloids into nanoformulations can overcome the said limitations paving the way for effective delivery of the alkaloids to the site of action in sufficient concentrations, which is crucial in tumour targeting. Our review attempts to assess whether alkaloid nanoformulation can be an effective tool in lung cancer therapy. The mechanism of action of each alkaloid having potential is explored in great detail in the review. In general, Alkaloids suppress oncogenesis by modulating several signaling pathways involved in multiplication, cell cycle, and metastasis, making them significant component of many clinical anti-cancerous agents. The review also explores the future prospects of alkaloid nanoformulation in lung cancer. So, in conclusion, alkaloid based nanoformulation will emerge as a potential gamechanger in treating lung cancer in the near future.